2018
DOI: 10.1038/s41598-018-22262-4
|View full text |Cite
|
Sign up to set email alerts
|

miR-27b regulates myogenic proliferation and differentiation by targeting Pax3 in goat

Abstract: This study found that miR-27 is expressed in muscle and regulates muscle proliferation and differentiation. We explored the function and regulatory mechanism of miR-27b in goat muscle proliferation and differentiation. Compared with the Boer goat, higher expression of miR-27b was observed in all of the collected muscle tissues of Anhuai goat, excluding the kidney, whereas the opposite expression pattern was observed for Pax3, which showed lower expression in Anhuai goat. Expression of miR-27b decreased gradual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 36 publications
(33 reference statements)
1
30
0
Order By: Relevance
“…mir-27b could modulate the expression of target genes at the posttranscriptional level (25,28,29). in the present study, we hypothesized whether mir-27b regulated the progression of ali through specific target genes.…”
Section: Discussionmentioning
confidence: 80%
“…mir-27b could modulate the expression of target genes at the posttranscriptional level (25,28,29). in the present study, we hypothesized whether mir-27b regulated the progression of ali through specific target genes.…”
Section: Discussionmentioning
confidence: 80%
“…Some studies have shown that miRNAs have an indispensable role in goat muscle development at different periods. For example, miR-27b was identified to inhibit the proliferation but promoted differentiation of skeletal muscle satellite via targeting PAX3 (Ling et al, 2018). And miR-487b-3p, which is significantly higher in the fetus than in adult, suppressed myoblast proliferation and differentiation by targeting IRS1 in skeletal muscle myogenesis (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, in seven different mouse muscle differentiation, or regeneration systems, we failed to detect the fusion. Considering the importance of Pax3 during myogenesis in mice and other mammals [2,13], and that the fusion shares similar downstream targets with the parental Pax3, we propose that the formation of the fusion may be a mechanism to escape certain microRNA regulation of the wild-type PAX3. Several recent studies also suggest that fusion genes can bypass microRNA-mediated regulation via changes of the 3′-UTR.…”
Section: Discussionmentioning
confidence: 95%
“…PAX3-FOXO1 has been reported to bind to the similar sites as wild-type PAX3, suggesting that the fusion targets similar downstream genes as parental PAX3 [5]. Given the critical role of Pax3 in the myogenesis of mice and other mammals [2,13], we then conjectured the possibility that the fusion in humans may substitute for the role Pax3 plays during myogenesis in mice.…”
Section: Pax3-foxo1 Is Absent In Mousementioning
confidence: 96%